2010
DOI: 10.1186/1471-2229-10-200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial-type phosphoenolpyruvate carboxylase expressed in male gametophyte of higher plants

Abstract: BackgroundPhosphoenolpyruvate carboxylase (PEPC) is a critical enzyme catalyzing the β-carboxylation of phosphoenolpyruvate (PEP) to oxaloacetate, a tricarboxylic acid (TCA) cycle intermediate. PEPC typically exists as a Class-1 PEPC homotetramer composed of plant-type PEPC (PTPC) polypeptides, and two of the subunits were reported to be monoubiquitinated in germinating castor oil seeds. By the large-scale purification of ubiquitin (Ub)-related proteins from lily anther, two types of PEPCs, bacterial-type PEPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 40 publications
1
59
0
Order By: Relevance
“…Arabidopsis seedlings and most tissues of the castor plant (Uhrig et al, 2008;O'Leary et al, 2011b), maize (Zea mays) roots and leaves (Prinsi et al, 2009), and lily (Lilium spp.) pollen (Igawa et al, 2010). Prinsi and coworkers (2009) showed that nitrate availability may influence monoubiquitination and phosphorylation of PTPC in maize roots and leaves, respectively.…”
Section: Influence Of In Vitro Dephosphorylation and Deubiquitinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis seedlings and most tissues of the castor plant (Uhrig et al, 2008;O'Leary et al, 2011b), maize (Zea mays) roots and leaves (Prinsi et al, 2009), and lily (Lilium spp.) pollen (Igawa et al, 2010). Prinsi and coworkers (2009) showed that nitrate availability may influence monoubiquitination and phosphorylation of PTPC in maize roots and leaves, respectively.…”
Section: Influence Of In Vitro Dephosphorylation and Deubiquitinationmentioning
confidence: 99%
“…In contrast, BTPC genes encode larger 116-to 118-kD polypeptides owing to a unique intrinsically disordered region that mediates BTPC's tight interaction with coexpressed PTPC subunits. This association results in the formation of unusual Class-2 PEPC heterooctameric complexes that are largely desensitized to allosteric effectors and that dynamically associate with the surface of mitochondria in vivo (O'Leary et al, 2009(O'Leary et al, , 2011aIgawa et al, 2010;Park et al, 2012).…”
mentioning
confidence: 99%
“…PEPC is found in all plants, green algae, and cyanobacteria, and in most archaea and nonphotosynthetic bacteria, but not in animals or fungi (Chollet et al, 1996;O'Leary et al, 2011a). Several isoforms of PEPC are present in plants, including planttype PEPCs and one bacterium-type PEPC (Sánchez and Cejudo, 2003;Sullivan et al, 2004;Mamedov et al, 2005;Gennidakis et al, 2007;Igawa et al, 2010). Arabidopsis (Arabidopsis thaliana) possesses three plant-type PEPC genes, AtPPC1, AtPPC2, and AtPPC3, and one bacteriumtype PEPC gene, AtPPC4.…”
mentioning
confidence: 99%
“…S3) are conserved among vascular plant BTPC orthologs, including the Arabidopsis BTPC, AtPPC4 (Hill et al, 2014). Thus, future studies need to determine if AtCPK4 and/or AtCPK11 participate in the in vivo regulatory phosphorylation of AtPPC4, particularly in developing pollen where AtCPK4, AtCPK11, and AtPPC4 are all highly expressed (Harper et al, 2004;Igawa et al, 2010). Extracts prepared from flowers of Col-0 plants but not from atcpk11 mutants showed Ca 2+ -dependent kinase activity against castor BTPC at Ser-451 suggesting that AtCPK11 is functionally as well as structurally homologous to RcCDPK1 (Fig.…”
Section: Sds-page (mentioning
confidence: 99%
“…Plant BTPC polypeptides and thus Class-2 PEPC complexes have only been documented in biosynthetically active tissues (i.e. developing seeds and pollen, immature leaves), as opposed to PTPCs that are constitutively expressed in the cytosol as housekeeping Class-1 PEPCs (Igawa et al, 2010;O'Leary et al, 2011aO'Leary et al, , 2011b. Although COS Class-1 PEPC localizes diffusely throughout the cytosol, the Class-2 PEPC associates with the outer mitochondrial envelope, an interaction mediated by its BTPC subunits .…”
mentioning
confidence: 99%